Cutting-edge innovations in bio-alcohol reforming: Pioneering pathways to high-purity hydrogen: A review - Liew, Wei Man; Nurul Aini, Razali (Elsevier, 2025)
The current review article discusses contemporary developments in the generation of hydrogen from bio-alcohols which include ethanol and glycerol, emphasizing the following primary processes: dry reforming (DR), sorption-enhanced steam reforming (SESR), and aqueous phase reforming (APR). These approaches give long-term paths to hydrogen by utilizing sustainable bio-alcohols. DR converts bio-alcohols and CO2 into syngas for carbon capture. However, it confronts problems such as elevated temperatures during operation and deactivation of the catalyst owing to coking. SESR combines CO2 capture with steam reforming for enhanced hydrogen purity and efficiency. However, this requires rigorous catalyst optimization. APR works at lower temperatures in water-based solutions, lowering energy consumption while generating hydrogen. The study discusses advances in catalyst design, process optimization, and the impact of nanostructured compounds for enhancing the production of hydrogen and lowering greenhouse gas emissions. The study emphasises the aforementioned technologies potential for long-lasting, high-purity hydrogen generation while simultaneously addressing the remaining technological challenges.